Analysis of Implementation Indonesia-Japan Economic Partnership Agreement (IJEPA) Toward Export Value Growth in Indonesia - Yuliati, Lilis; Komariyah, Siti; Khusnul Khatimah, Diah Ayu (Jurnal Economia, 2023)
This study aims to analyze the impact of the Indonesia-Japan Economic Partnership Agreement (IJEPA) bilateral trade agreement on Indonesia's export value in the long term. The secondary data time series used for the research is from 2005Q1 to 2019Q4, and the research method employed is the VECM (Vector Error Correction Model). The results of the VECM analysis show that the IJEP bilateral agreement has a significant negative effect, the inflation variable has a significant positive effect, and the FDI and exchange rate variables have a negative but not significant effect on the value of Indonesia's exports to Japan. Implementation of the recommended policies to increase export value and economic growth, namely compliance with product standardization, especially for destination countries, actively and openly providing information related to the IJEPA tariff scheme and utilizing capacity building.